An Investigation of the Use of Polyaniline (PANI)/Chlorine-Doped Graphene Oxide (Cl-GO)/Lead(IV)Oxide Composite Electrodes in Supercapacitor Systems - Akyol, Aleyna Beyza; Semiz, Nimet; Sevinc, Yagmur; Serim, Rukiye; Akgul, Doga; Coban, Berk; Gencten, Metin (ELECTROCHEMICAL SOC INC, 2025)
Ternary composites consisting of polyaniline (PANI), chlorine-doped graphene oxide (Cl-GO), and lead dioxide (lead(IV)oxide, PbO2) were synthesized, and their use as electrode materials in asymmetric-type supercapacitors was investigated. Cl-GO was synthesized through a one-step process at room temperature using the chronoamperometric method, while PANI was prepared via chemical synthesis. Two distinct systems were fabricated using different electrolytes: 1.0 M H2SO4 for the PPGO1 system and 1.0 M KOH for the PPGO2 system. The conductive polymer and heteroatom-doped graphene oxide were characterized using spectroscopic and microscopic techniques. X-ray photoelectron spectroscopy and Fourier-transform infrared (FT-IR) analyses confirmed the successful synthesis of heteroatom-doped graphene oxide, and the FT-IR spectrum of PANI confirmed the successful formation of polyaniline. Field-emission scanning electron microscopy images of the synthesized components demonstrated that they were successfully produced. Fabricated supercapacitors were characterized using cyclic voltammetry, galvanostatic charge-discharge, and electrochemical impedance spectroscopy. At a scan rate of 10 mV s-1, the supercapacitor fabricated using the Cl-GO/PANI/PbO2 electrode exhibited specific capacitance values of 97 mF cm-2 for PPGO1 and 54 mF cm-2 for PPGO2. These results highlight the potential of this material as a promising electrode for future high-performance, fast-charging, and long-life supercapacitor applications.
Keywords: Supercapacitor; Ternary composites; Chlorine-doped graphene oxide; Polyaniline; Lead dioxide; Materials Science; Physics